The knight and the moth - Gillig, Rachel (Gillig, Rachel. Stonewater Kingdom, 2025)
"Sybil Delling has spent nine years dreaming of having no dreams at all. Like the other foundling girls who traded a decade of service for a home in the great cathedral, Sybil is a Diviner. In her dreams she receives visions from six unearthly figures known as Omens. From them, she can predict terrible things before they occur, and lords and common folk alike travel across the kingdom of Traum's windswept moors to learn their futures by her dreams. Just as she and her sister Diviners near the end of their service, a mysterious knight arrives at the cathedral. Rude, heretical, and devilishly handsome, the knight Rodrick has no respect for Sybil's visions. But when Sybil's fellow Diviners begin to vanish one by one, she has no choice but to seek his help in finding them. For the world outside the cathedral's cloister is wrought with peril. Only the gods have the answers she is seeking, and as much as she'd rather avoid Rodrick's dark eyes and sharp tongue, only a heretic can defeat a god"--